Bond strength of dentin submitted to bleaching and restored with different materials - Nelize Marcelino Pessarello; Yara T. Correa Silva-Sousa; Fuad Jacob Abi Rached-Junior; Aline Evangelista Souza-Gabriel (Revista Sul-Brasileira de Odontologia, 2013)
The use of adhesive composite resin with fluoride and with greater fluidity can be favorable to the restoration of the palatal/lingual face of teeth submitted to internal bleaching. Objective: This study evaluated the bond strength of adhesive systems and composite resins to bleached dentin. Material and methods: Forty maxillary canines were sectioned to obtain 40 blocks (5 x 5 mm) of intracoronary dentin. The fragments were included and bleached with 37% carbamide peroxide. After 7 days, the specimens were divided into two groups according to the adhesive system: with (Optibond Solo Plus) and without (Single Bond) fluoride and subdivided into 2 subgroups (n = 10) according to the composite resin: microhybrid (Z250) and flowable (Z350). The restoration was carried out through a bipartite matrix. After 24 hours, the specimens were subjected to shear bond strength test. The data (MPa) were analyzed by ANOVA and Tukey test (α = 0.05). Results: The best results (p < 0.05) were obtained for fluoridated adhesive (7.44 ± 2.35) compared with that without fluoride (5.36 ± 2.01); flowable resin (7.76 ± 2.23) performed better than microhybrid resin (5.03 ± 1.72). When the two variables were associated, the highest results were obtained for the specimens restored with fluoridated adhesive and flowable resin (9.04 ± 1.92). Lower results were observed for non-fluoridated adhesive + microhybrid resin – control (4.24 ± 1.59), without statistically significant differences when compared with the fluoridated adhesive + microhybrid resin (5.83 ± 1.52). Conclusion: The combination with fluoridated adhesive and flowable resin increases the shear bond strength of bleached dentin.